An immune cocktail therapy to realize multiple boosting of the cancer-immunity cycle by combination of drug/gene delivery nanoparticles - Jiayan Wu; Jie Chen; Yuanji Feng; Sijia Zhang; Lin Lın; Zhaopei Guo; Pingjie Sun; Caina Xu; Huayu Tian; Xuesi Chen (2020)
Immune checkpoint blockade therapy (ICT) has shown potential in the treatment of multiple tumors, but suffers poor response rate in clinic. We found that even combining ICT with chemotherapy, which was wildly used in clinical trials, failed to achieve satisfactory tumor inhibition in the B16F10 model. Thus, we further constructed a previously unexplored immune cocktail therapy and realized multiple boosting of the cancer-immunity cycle. Cocktail therapy consisted of two kinds of tumor microenvironment-responsive drug and gene delivery nanoparticles to achieve specific delivery of doxorubicin and codelivery of plasmids expressed small hairpin RNA of PD-L1 (pshPD-L1) and hyaluronidase (pSpam1) in the tumor area. Experimental evidences proved that any component in the cocktail therapy was indispensable, and the cocktail therapy exhibited excellent antitumor effects against different types of tumors. The cocktail therapy presented here offers a searching strategy for more synergistic units with ICT and is meaningful for developing more efficient antitumor immunotherapy.